Nurses' Knowledge Level in Fall Risk Assessment in the Inpatient Wards of a Private Hospital, Pekanbaru - Ramadhan, Intan Tiara; Adelia, Gita; Herniyanti, Rina; Putra, Ifon Driposwana; Malfasari, Eka; Saputra, Candra; Puswati, Desti (REAL in Nursing Journal, 2025)
Background: Patient Safety Goal (PSG) 6 related to the risk of falls is still a worrying issue, especially for hospitalized patients in hospitals. One of the efforts to minimize the risk of falls is through knowledge. Previous research found that nurses' knowledge about patient safety still varies in various hospitals in general and hospital service units in particular.Purpose: The purpose of this study was to analyze nurses' knowledge level in fall risk assessment in the inpatient room of a private hospital in Pekanbaru.Methods: This research is a quantitative study with a descriptive approach, conducted from August 2024 to January 2025. The sampling technique used is accidental sampling, with a total sample of 68 nurses working in inpatient wards. The instrument used is a questionnaire on nurses' knowledge of patient safety.Results: The results of this study show that almost all respondents are in the age range of 18 to 40 years, with a total of 54 respondents (79.4%), almost all respondents are female, as many as 56 people (82.4%). In terms of education, more than half of the respondents had a Diploma educational background, with a total of 39 people (57.4%). The results showed that almost all nurses involved in this study had good knowledge about patient safety with a total of 64 nurses (94.1%).Conclusion: Nurses' knowledge about patient safety is quite good. However, it is important to continue to improve nurses' knowledge and awareness through training and continuing education to minimize the risk of falls in the hospital.